Discontinuous rate-stiffening in a granular composite modeled after cornstarch and water - David Z. Chen (Nature Portfolio, 2019)
Cornstarch and water is a mixture that solidifies under impact. The authors find that ordinary sand behaves in a similar way when coated with a thin layer of viscoelastic polymer, suggesting a potential route for designing materials which respond dramatically to fast deformations.